2022
DOI: 10.1038/s41598-022-12613-7
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept for multiplex amplicon sequencing for mutation identification using the MinION nanopore sequencer

Abstract: Rapid, cost-effective identification of genetic variants in small candidate genomic regions remains a challenge, particularly for less well equipped or lower throughput laboratories. The application of Oxford Nanopore Technologies’ MinION sequencer has the potential to fulfil this requirement. We demonstrate a proof of concept for a multiplexing assay that pools PCR amplicons for MinION sequencing to enable sequencing of multiple templates from multiple individuals, which could be applied to gene-targeted diag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…When the reads in the region near the premature termination codon were examined, a frameshift caused by missing a nucleotide in a run of homopolymers was frequently found. For the MinION platform, 60-fold or higher read coverage has been found to result in a better than 99.95% sequencing accuracy [29] [30]. In our study, Method K resulted in the identical sequence in two samples (245467 and 246038) when compared to the sequence generated from the same samples on the MiSeq (Supplementary Figures 2a-h & 4a-h).…”
Section: Kits No Mutations Methodsmentioning
confidence: 51%
“…When the reads in the region near the premature termination codon were examined, a frameshift caused by missing a nucleotide in a run of homopolymers was frequently found. For the MinION platform, 60-fold or higher read coverage has been found to result in a better than 99.95% sequencing accuracy [29] [30]. In our study, Method K resulted in the identical sequence in two samples (245467 and 246038) when compared to the sequence generated from the same samples on the MiSeq (Supplementary Figures 2a-h & 4a-h).…”
Section: Kits No Mutations Methodsmentioning
confidence: 51%
“…Although the main problem with nanopore sequencing is its still relatively high per-base error rate in raw reads compared to other sequencing techniques, these are offset by the high coverages obtained and good bioinformatics handling [ 56 ]. Previous reports indicate that a 100× coverage is adequate to establish an accurate genotype; furthermore, advances in nanopore sequencing technology, in combination with a dedicated data analysis pipeline and good coverage, have proven to be comparable in performance to conventional Sanger sequencing applied to PCR amplicons, as is the case in this work [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 84%
“…Taxonomic classification with the amplicon data can be challenging even with longer amplicons 24 , which is especially useful for lineage tracing 25 . In addition, amplification efficiency among different amplicon regions might vary significantly, depending on the sequence complexity length of the amplicon and GC content 26 . In our study, among the 19 targeted regions, Rv0678 showed the highest amplification efficiency (with 981,074 coverage), while rspA showed the lowest (with 166.522 coverage) ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%